Sixty-four or four-and-sixty? The influence of language and working memory on children's number transcoding - Imbo, Ineke; Vanden Bulcke, Charlotte; De Brauwer, Jolien; Fias, Wim (Frontiers in Psychology, 2014)
Number transcoding (e.g., writing 64 when hearing ‘sixty-four’) is a basic numerical skill; faultlessly performed in adults, but rather difficult for children. In the present study, children speaking Dutch (an inversed number language) and French (a non-inversed number language) wrote Arabic digits to dictation. We also tested their IQ and their phonological, visuospatial, and executive working memory. Although the amount of transcoding errors (e.g., hearing 46 but writing 56) was equal in both groups, the amount of inversion errors (e.g., hearing 46 but writing 64) was significantly higher in Dutch-speaking than in French-speaking children. Regression analyses confirmed that language was the only significant predictor of inversion errors. Working-memory components, in contrast, were the only significant predictors of transcoding errors. Executive resources were important in all children. Less-skilled transcoders also differed from more-skilled transcoders in that they used semantic rather than asemantic transcoding routes. Given the observed relation between number transcoding and mathematics grades, current findings may provide useful information for educational and clinical settings.